Autophagy of the m6A mRNA demethylase FTO is impaired by low-level arsenic exposure to promote tumorigenesis - Yan-Hong Cui (Nature Portfolio, 2021)
RNA m6A demethylase FTO has oncogenic roles in cancers. Here the authors show that chronic low-level exposure of arsenic inhibits autophagic degradation of FTO, leading to FTO stabilisation and reduced m6A RNA methylation in keratinocytes and its subsequent malignant transformation.